Prevalence and characterisation of size and sequence-based microvariant alleles at nine autosomal STR markers in the Central Indian population - Dash, Hirak Ranjan; Vajpayee, Kamayani; Srivastava, Ankit; Das, Surajit (Annals of human biology, 2021)
Though microvariant alleles are widely reported in global populations, they are not well characterised to date. To study the prevalence and characterisation of size and sequence-based microvariant alleles Next Generation Sequencing (NGS) was used to sequence microvariant alleles at nine autosomal STR markers in 138 samples. After sequencing 31 STR markers using Precision ID GlobalFilerTM NGS STR panel v2, only nine markers, i.e. D12S391, D19S433, D1S1656, D21S11, D2S441, D7S820, FGA, Penta D, and TH01 showed the prevalence of microvariant alleles. Occurrence of microvariant alleles was positively correlated with Total Possible Alleles (p < 0.005), Power of Discrimination (p < 0.01), Polymorphic Information Content (p < 0.01), and Power of Exclusion (p < 0.05) and negatively correlated with the Matching Probability (p < 0.01). The average allele frequency of the microvariant alleles was found to be significantly less than the allele frequency value of the complete alleles (p = 0.88). Further, sequencing of these microvariant alleles reveals the deletion of nucleotides from the start, end, or middle of the repeat unit is responsible for the generation of a microvariant allele. Prevalence of microvariant alleles is rare in nature and is limited to 9 STR loci out of 31 STR loci tested in the central Indian population. The occurrence of microvariant alleles in a locus increases its forensic and paternity application.